Visual Parody of Decolonization: Reading the Hybridity of Colonial Symbols in the “Tujuh Belasan” Commemorations - Dektisa, Andrian (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
ABSTRACT Indonesia’s Independence Day celebrations—popularly known as Tujuh Belasan—often feature theatrical performances that restage battles between Japanese troops, Allied forces, and Indonesian freedom fighters. In these performances, military costumes and props are crafted manually by local hands, turning narrow village alleys into symbolic stages. While they may appear to be mere entertainment, such reenactments, when viewed through the lens of complex postcolonial understanding, function as visual parodies of decolonization. Drawing on Homi K. Bhabha’s concepts of mimicry and the third space, these performances expose ironic fissures that unsettle colonial authority. They transform colonial imagery from symbols of domination into objects of mockery, hybridity, and creative contestation. Through Gillian Rose’s notion of the site of production, this study highlights how the making of costumes and theatrical paraphernalia generates visual meaning beyond institutional control, embedding local participation and creativity in the reinterpretation of history. This research employs a qualitative approach combining visual studies and ethnographic observation to examine how vernacular visual forms negotiate power, memory, and identity. The result is a form of visual parody that acts as a grassroots strategy of decolonizing historical imagination—using design as a tool to subvert dominant colonial narratives and to reconstruct the past in ways that are playful, hybrid, and deeply rooted in local collective agency. ABSTRAK Perayaan Hari Kemerdekaan Indonesia yang populer disebut Tujuh Belasan sering menampilkan pertunjukan teatrikal yang merekonstruksi pertempuran antara pasukan Jepang, Sekutu, melawan pejuang kemerdekaan Indonesia. Di pertunjukan itu kostum dan properti militer dibuat secara manual oleh tangan-tangan lokal yang mengubah lorong perkampungan menjadi panggung simbolik. Walau tampak sebagai hiburan semata, pertunjukan itu dalam perspektif pemahaman pascakolonial yang kompleks adalah bentuk parodi visual terhadap dekolonisasi. Menggunakan konsep mimicry dan third space dari Homi K. Bhabha, reenactment semacam itu mempertontonkan celah-celah ironis yang mengguncang otoritas kolonial. Menjadikan citra-citra kolonial bukan lagi simbol dominasi, melainkan objek olok-olok, hibriditas, dan perebutan makna secara kreatif. Melalui konsep site of production dari Gillian Rose, penelitian ini menyoroti bagaimana proses produksi kostum dan pernak-pernik impresi teatrikal membentuk makna visual di luar kendali institusional, menanamkan partisipasi dan kreativitas lokal dalam penafsiran ulang sejarah. Penelitian ini kualitatif melalui studi visual dan observasi etnografis, yang mengkaji bagaimana bentuk-bentuk visual vernakular bernegosiasi dengan kekuasaan, ingatan, dan identitas. Hal itu menjadi ungkapan parodi visual yang berfungsi sebagai strategi dekolonisasi imajinasi sejarah yang muncul dari bawah. Dimana menjadikan desain sebagai alat untuk menumbangkan narasi dominan kolonial dan merekonstruksi masa lalu secara jenaka, hibrid, dan penuh agensi kolektif khas lokalitas.